PENERAPAN PERMAINAN BISIK BERANTAI UNTUK MENGEMBANGKAN BAHASA ANAK USIA 5-6 TAHUN - Lutfia Gunawan, Aisyah; Nopriansyah, Untung; Lutfia Gunawan , Aisyah (Bunayya, 2026)
The development of early childhood language skills is an important aspect that needs to be stimulated through learning activities that are appropriate to the child's characteristics. This study aims to describe the application of the chain whisper game in developing the language skills of children aged 5–6 years. This study used a descriptive qualitative method at Thoyyibah Kindergarten, Bandar Lampung, with 15 children and their class teacher as subjects. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that the chain whisper game was able to develop children's language skills, especially in the aspects of listening and speaking. Based on the results of observations, 13 of the 15 children (86.7%) were able to listen and understand the message well, while 10 of the 15 children (66.7%) were able to convey the message verbally with more confidence. However, there were still obstacles such as concentration, listening skills, and differences in language skills between children.